Understanding OCD : skills to control the conscience and outsmart obsessive compulsive disorder - Shapiro, Leslie (Santa Barbara, California : Praeger, an imprint of ABC-CLIO, LLC, 2015)
"One of the most experienced therapists in the world for treatment-resistant obsessive compulsive disorder (OCD) explains the disorder, the treatments available, and the skills needed to overcome and outsmart OCD. This is an eye-opening study of one of the most common psychiatric ailments diagnosed today--obsessive compulsive disorder (OCD). Written by Leslie J. Shapiro, a renowned therapist at one of the most well known OCD facilities in the world, this reference shares effective treatment strategies and clinical factors for helping therapists, mental health professionals, psychology students, clergy, and others deal with patients coping with this illness. The author offers case examples from her 15 years of residential work with patients, demonstrating how sufferers--even the most treatment resistant--can get control of the condition. Organized into three sections, this guidebook first reveals how OCD and guilt are intertwined and explores survival instincts, cultural factors, and the nature of thoughts. The second section covers aspects of the obsessive conscience such as scrupulosity, moralosity, and obsessive guilt. The book's conclusion describes effective exposure and response prevention strategies for these symptoms and examines methods of treatment that augment and help maintain recovery. An in-depth discussion on the differences between compulsive and impulsive behaviors--as well as other treatment impediments--is included." --
"This title represents Shapiro's decades of experience with effective treatment for OCD by outlining the biologic basis of OCD and discussing how the illness hijacks the conscience"--
Your brain has a mind of its own -- Hypersurvival : evolutionary survival instincts gone awry--too much of a necessary thing? -- All walks of life : global prevelance and the universal culture of rituals -- We all have "bad" thoughts -- In good company : a who's who of obsessive conscience -- Scrupulosity : it's not religious -- Moralosity : nonreligious and moral perfectionistic OCD -- Obsessive guilt -- Taking control where you can and must -- Helpful treatment augmentations -- It's impulsive, not compulsive -- A word about countertransference -- Appendix A: Glossary -- Appendix B: Types of guilt found in Western literature -- Appendix C: Harder personal feelings questionnaire -- Appendix D: Rate your OCD -- Appendix E: Pennsylvania inventory of scrupulosity -- Appendix F: The Loyola religious obsession and compulsion checklist -- Appendix G: Family accommodation scale for obsessive-compulsive disorder.
Includes bibliographical references and index.
Keywords: Obsessive-compulsive disorder -- Treatment; Obsessive-compulsive disorder